Analysis of hemostasis parameters at preeclampsia of the various severity - Мариам, Бен Амор; Гнатко, Елена Петровна; Турос, Елена Игоревна; Брезицкая, Нина Владимировна (ScienceRise: Medical Science, 2016)
Preeclampsia it is a serious complication of pregnancy that is a main cause of maternal perinatal morbidity and lethality. In multifactorial genesis of development of this state the main role is played by homeostasis disturbance. Aim of research: to assess the parameters of hemostasis system in pregnant with preeclampsia of the different severity using the risk factors, genetic polymorphism of folate metabolism genes and blood coagulation. Material and methods of research. There were examined 155 pregnant women of reproductive age in 3 trimester of pregnancy: 123 – with preeclampsia of the different severity and 32 – with physiological pregnancy course (control). The analysis of risk factors was carried out by the elaborated questionnaire with point assessment. There were studied the genes of folate cycle (MTHFR C677T, MTRR ІІ22Met (66-a-g) and coagulation factors (F5 G1691A, F2 G20210A). There were assessed the parameters of quantity of platelets, fibrinogen level, values of prothrombin index (PTI), international normalized ratio (INR), activated partial thromboplastin time (APTT). The results were processed using the programs of processing of electric tables «Excel 7,0 for Windows XP». Results. It was established, that the expressed changes (decrease of platelets quantity, increase of fibrinogen level, increase of PTI value, decrease of INR and APTT) were noted in pregnant women that had the high point (≥5) of preeclampsia risk factors, early clinical manifestations of these complication (up to the 34 week of pregnancy), gene polymorphism (heterozygous variant of studied polymorphisms and their complication). There was noted the correspondence between the hemostasis system and severity degree of given complication. Conclusions. Analysis of values of parameters of hemostasis system in pregnant women with preeclampsia in the third trimester taking into account the risk factors and genetic predisposition has a prognostic value for the assessment of obstetric and perinatal risk and choice of tactics of conducting pregnancy and delivery